Reliability, validity, and factorial structure of the Turkish version of the Empathy Quotient (Turkish EQ). Issue 3 (3rd July 2018) - Kose, Samet; Celikel, Feryal Cam; Kulacaoglu, Filiz; Akin, Ercan; Yalcin, Mehmet; Ceylan, Vedat
ABSTRACT: OBJECTIVES: Empathy is an essential ability that allows us to tune into how others are feeling or thinking. Empathy makes it possible to resonate with others' positive and negative feelings alike so that we can thus feel happy when we vicariously share the joy of others and we can share the experience of suffering when we empathize with someone in pain. Empathy training not only promotes prosocial behaviour, but also augments positive affect and resilience, which in turn fosters better coping with stressful situations. The Empathy Quotient (EQ) is a self-report questionnaire that was developed to measure the cognitive, affective, and behavioural aspects of empathy. Here, we aimed to examine the validity, reliability, and factor structure of the EQ in a Turkish sample. METHODS: Participants were 436 mostly college students and civil servants (195 female, 241 male). Sociodemographic information, the Turkish version of the EQ, Marlowe-Crowne Social Desirability Scale (MC-SDS) 33-item full version and MC-SDS 13-item shorter versions were administered. All statistical analyses were performed by using SPSS version 23 for Windows. RESULTS: EQ scores were significantly higher in female participants ( Female  = 46.45, SDFemale  = 0.62) compared to the male participants ( Male  = 43.68, SDMale  = 0.56). The Cronbach's alpha coefficient for the scale was 0.76, Guttman's split-half reliability coefficient was 0.61, and test–retest reliability coefficient was 0.95. A positive and statistically significant correlation was found between the Turkish EQ and MC-SDS Full version ( r  = 0.299, p  < .01) and short form of MC-SDS ( r  = 0.273, p  < .01). A three-factor solution that accounted for 25.28% of the variance observed. CONCLUSIONS: The Turkish version of the EQ has satisfactory validity, good internal and test–retest reliability with a robust factorial structure to use in a clinical population in Turkey. Moreover, as predicted, women scores were statistically significantly higher on the EQ than men. This result was consistent with a series of earlier studies reporting gender differences (female superiority) on questionnaires that measure empathy. A better knowledge of empathy will have important implications for the examination and understanding of certain neurological and psychiatric disorders, including autism, narcissistic and antisocial personality disorders, and may also provide important clues about the relevant brain circuitry underlying empathy.